Pengaruh Kompetensi, Motivasi Kerja Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT. Kayamas Intitama Semarang - Daniel Imam Hari Basuki; Darsono Darsono (Jurnal Ekonomi Manajemen Akuntansi, 2022)
This study aims to analyze "The Influence of Competence, Work Motivation and Career Development on Employee Performance at PT Kayamas Intitama Semarang". Methods of data collection using a questionnaire. The sampling technique used random sampling technique. A sample of 60 respondents is an employee at PT Kayamas Intitama Semarang. Based on the results of the study, the competence variable has a positive effect on employee performance. This is indicated by the calculated t value that is greater than the t table, namely 5.608 > 1.672, with a sig value. of 0.000 <0.05 (significant). The magnitude of β1 0.402 (positive sign) means that the higher the competence, the higher the employee's performance. Work motivation has a positive effect on employee performance. This is with the calculated t value of 6.400 > t table, namely 1.672 with a sig. of 0.000 <0.05 (significant). The magnitude of β2 is 0.467 (positive sign), meaning that the better the work motivation, the higher the employee performance. Career development has a positive effect on employee performance. This is indicated by the calculated t value which is equal to 5.042 > t table which is 1.672 with a sig value. of 0.000 <0.05 (significant). The magnitude of β3 is 0.345 (positive sign), meaning that the higher the employee's career development, the higher the employee's performance.